Meta-Analysis and Systematic Review of the Thermal Stress Response: Gallus gallus domesticus Show Low Immune Responses During Heat Stress - Siddiqui, Sharif Hasan; Khan, Mousumee; Kang, Darae; Choi, Hyun Woo; Shim, Kwanseob (Frontiers in Physiology, 2022)
Heat stress, which affects broiler growth performance and immunity, is a major concern in the poultry industry. The aim of this meta-analysis was to demonstrate the significant effect of heat stress on broiler weight gain and immunoglobulin levels, which regulates the mortality rate of broilers. A total of 2585 studies were downloaded from PubMed, Web of Science, and Google Scholar from January 1, 2015, to September 1, 2021. Eventually, 28 studies were selected based on specific criteria. The results for body weight gain, total weight of immune organs (thymus, spleen, and bursa of Fabricius), immunoglobulin (IgA, IgG, and IgM) levels, and mortality rate were analyzed using odds ratio or the random-effects model (REM) at a confidence interval (CI) of 95%. Compared to the control, heat stress significantly decreased body weight gain (10 trials: REM = 1.35, 95% CI: 1.21, 1.50). Compared to that in the control, heat stress significantly increased immunoglobulin levels: IgA (7 trials: REM = 1.69, 95% CI: 0.90, 3.16), IgG (6 trials: REM = 1.24, 95% CI: 0.85, 1.81), IgM (8 trials: REM = 0.69, 95% CI: 0.44, 1.08), and heat stress also increased the broiler mortality rate (6 trials: REM = 0.06, 95% CI: 0.01, 0.27). However, there were no significant changes in the immune organs between the control and heat-stressed groups. In conclusion, heat stress remarkably alters the weight gain and immune function of broilers, which leads to increased mortality.